SERPINA2 is a novel gene with a divergent function from SERPINA1. - Patrícia Isabel Marques (PLoS ONE, 2013)
Serine protease inhibitors (SERPINs) are a superfamily of highly conserved proteins that play a key role in controlling the activity of proteases in diverse biological processes. The SERPIN cluster located at the 14q32.1 region includes the gene coding for SERPINA1, and a highly homologous sequence, SERPINA2, which was originally thought to be a pseudogene. We have previously shown that SERPINA2 is expressed in different tissues, namely leukocytes and testes, suggesting that it is a functional SERPIN. To investigate the function of SERPINA2, we used HeLa cells stably transduced with the different variants of SERPINA2 and SERPINA1 (M1, S and Z) and leukocytes as the in vivo model. We identified SERPINA2 as a 52 kDa intracellular glycoprotein, which is localized at the endoplasmic reticulum (ER), independently of the variant analyzed. SERPINA2 is not significantly regulated by proteasome, proposing that ER localization is not due to misfolding. Specific features of SERPINA2 include the absence of insoluble aggregates and the insignificant response to cell stress, suggesting that it is a non-polymerogenic protein with divergent activity of SERPINA1. Using phylogenetic analysis, we propose an origin of SERPINA2 in the crown of primates, and we unveiled the overall conservation of SERPINA2 and A1. Nonetheless, few SERPINA2 residues seem to have evolved faster, contributing to the emergence of a new advantageous function, possibly as a chymotrypsin-like SERPIN. Herein, we present evidences that SERPINA2 is an active gene, coding for an ER-resident protein, which may act as substrate or adjuvant of ER-chaperones.